The Implementation of Metacognitive Learning Model to Improving The Motivation and TIK Learning Results of The Student of VII Grade at SMP 6 Singaraja In the Academic Year 2011/2012 - Budhi Sentosa, I Putu (Universitas Pendidikan Ganesha, 2013)
The aims of this class action research are: (1) to know the enhancement of the TIK learning motivation of the student of VII A2 grade at SMP 6 Singaraja by using metacognitive learning model, (2) to know the TIK learning result of VII A2 grade at SMP 6 Singaraja by using metacognitive learning model and (3) to know the response of VII A2 grade at SMP 6 Singaraja in using metacognitive learning model in TIK learning.This research is a class action research consists of two cycles. Each cycle has four steps that are action plan, action implementation, observation and evaluation, and reflection. The research subject is the 35 students of VII A2 grade at SMP 6 Singaraja; while the research object are 1 learning motivation of the student, (2) the result of the learning, 3 the student response in TIK learning by the application of metacognitive learning model. The data collection of the result TIK learning are collected by test method and observation, and also the data of student response are collected by questionnaire report. The data collection are analyzed using descriptive analysis.The results of this research indicate that the learning result of students has increased, in the first cycle for the average value of learning result and students classical completeness percentage that is equal to 73,76% and 68,57 % in the second cycle to be 77,76 and 77,14%. Similarly students motivation has increased, in the first cycle isÂ the average score was 58,71 in the high category on the second cycleÂ was 61,14 in the high category. Besides that, the student response in using metacognitive learning model is positive to average score 62,37. Â